2018
DOI: 10.1101/415745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A synthetic biology platform for the reconstitution and mechanistic dissection of LINC complex assembly

Abstract: Condensed title:Reconstituting functional SUN proteins in artificial nuclear membranes. ABSTRACT (180/180 words)The linker of nucleoskeleton and cytoskeleton (LINC) is a conserved nuclear envelope-spanning molecular bridge that is responsible for the mechanical integration of the nucleus with the cytoskeleton. LINC complexes are formed by a transluminal interaction between the outer and inner nuclear membrane KASH and SUN proteins, respectively. Despite recent structural insights, our mechanistic understanding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…For example, in vitro reconstituted LINC complexes on artificial nuclear membranes indicate that SUN2 contains a single transmembrane domain while SUN1 has three [41]. In addition, hydrophobic patches in the nucleoplasmic region of SUN proteins may associate with the inner nuclear membrane and the lamin network to distribute forces inside the nucleus [41]. Additional studies are required to determine how SUN and KASH domains might be directly interacting with the outer nuclear membrane.…”
Section: Other Factors That Influence Force Transmission Through Lincmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in vitro reconstituted LINC complexes on artificial nuclear membranes indicate that SUN2 contains a single transmembrane domain while SUN1 has three [41]. In addition, hydrophobic patches in the nucleoplasmic region of SUN proteins may associate with the inner nuclear membrane and the lamin network to distribute forces inside the nucleus [41]. Additional studies are required to determine how SUN and KASH domains might be directly interacting with the outer nuclear membrane.…”
Section: Other Factors That Influence Force Transmission Through Lincmentioning
confidence: 99%
“…Recent studies suggest possible mechanisms for LINC complexes to assemble into larger structures., Mammalian SUN1 proteins form oligomers larger than trimers detected in living cells by fluorescence fluctuation spectroscopy [49]. SUN1 has also been observed to form clusters in a reconstituted, cell-free expression system on artificial lipid bilayers [41]. Computer modeling predicts that SUN1 trimers can associate with each other laterally through their SUN domains to form higher-order clusters [41,43].…”
Section: Other Factors That Influence Force Transmission Through Lincmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we developed a simple bottom-up synthetic biology platform based on a mammalian cell-free expression (CFE) system for the rapid reconstitution and study of LINC complex assembly using full-length SUN proteins (7). The most abundant isoforms of SUN proteins (SUN1 and SUN2) from mouse were expressed in the presence of supported lipid bilayers with excess membrane reservoirs (SUPER) templates (8) to mediate spontaneous reconstitution.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging paradigm for membrane engineering relies on the synthesis and incorporation of membrane proteins in situ by the means of a cell‐free expression system. Both prokaryotic and mammalian cell‐free expression systems have been shown to successfully express structurally intact membrane proteins in mixed micelles or lipid bilayers (Shinoda et al, 2016; Majumder, Willey, et al 2019). Also, it has been demonstrated that mechanosensitive channel proteins can be successfully expressed and incorporated into synthetic cells (Garamella, Majumder, Liu, & Noireaux, 2019; Hindley et al, 2019; Majumder et al, 2017).…”
Section: The Boundary Of Synthetic Cellsmentioning
confidence: 99%